2019
DOI: 10.1530/rep-19-0150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of murine amniotic fluid B cells in normal pregnancy and in preterm birth

Abstract: The amniotic fluid provides mechanical protection and immune defense against pathogens to the fetus. Indeed, components of the innate and adaptive immunity, including B cells, have been described in the amniotic fluid. However, limited information concerning phenotype and functionality of amniotic fluid B cells is available. Hence, we aimed to perform a full phenotypical and functional characterization of amniotic fluid B cells in normal pregnancy and in a mouse model of preterm birth. Phenotypic analysis depi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Bommer at al. reported on an increase of B cells in the amniotic fluid following LPS injection and suggested that B cells may serve as an immunological protective barrier against PTB [45]. Earlier studies found that administration of high-dose LPS i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Bommer at al. reported on an increase of B cells in the amniotic fluid following LPS injection and suggested that B cells may serve as an immunological protective barrier against PTB [45]. Earlier studies found that administration of high-dose LPS i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The AF, a crucial component of the intrauterine environment, is known to harbor a diverse population of immune cells that play a pivotal role in maintaining maternal-fetal tolerance and protecting against intrauterine infections [70]. Among the various immune cells present in the AF, macrophages, neutrophils, T cells, B cells, and natural killer cells have been identified as key players in orchestrating immune responses within the gestational compartment [71][72][73]. However, we only identified macrophage in cultured AFCs from fetuses with NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Recent studies have identified the critical role of B cells in birth timing and preterm birth in animals and humans. [69][70][71] In mice, the expression level of EBF1 at the mRNA level is downregulated in splenic B cells during normal pregnancies. 72 Low EBF1 mRNA has been associated with an increased risk of sPTB in humans due to altered maternal-fetal immune and cell cycle/apoptosis pathways.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…EBF1 is essential for B cell development and control of blood pressure 67,68 . Recent studies have identified the critical role of B cells in birth timing and preterm birth in animals and humans 69–71 . In mice, the expression level of EBF1 at the mRNA level is downregulated in splenic B cells during normal pregnancies 72 .…”
Section: Family‐based and Epidemiological Evidence For Preterm Birthmentioning
confidence: 99%